A new species of Polylepis (Rosaceae) from Santuario Nacional Pampa Hermosa, Peru - Quispe-Melgar, Harold Rusbelth; Llacua-Tineo, Yashira Stefani; Ulloa Arias, Nathaly Estela; Kessler, Michael (Phytotaxa, 2024)
A new species of Polylepis from central Peruvian province of Tarma and present in Santuario Nacional Pampa Hermosa, is described and illustrated. The new species is most similar to Polylepis canoi but differs by its 3-foliate leaves, smaller oblong-lanceolate auriculate and sessile leaflets, shorter petioles with glandular hairs of reddish yellow resin, shorter pendulous axillary inflorescences 8–14 cm long with 6–13 flowers, and higher number of stamens (17–24). On present knowledge, the species has a tiny distribution and is further threatened by land use practices, so that we classify it as critically endangered. This discovery reinforces our understanding of the central Peruvian Andes as a poorly known center of biodiversity and endemism.